2020
DOI: 10.1177/1179551420915856
|View full text |Cite
|
Sign up to set email alerts
|

Predicting Healthy Lifestyle Behaviours Among Patients With Type 2 Diabetes in Rural Bali, Indonesia

Abstract: Background: Type 2 diabetes is a lifelong metabolic disease closely related to unhealthy lifestyle behaviours. This study aimed to identify factors explaining the healthy lifestyle behaviours of patients with type 2 diabetes in rural Indonesia. The extended health belief model, demographic characteristics, clinical lifestyle factors and diabetes knowledge were investigated to provide a complete description of these behaviours. Method: A sample of 203 patients with type 2 diabetes representing a cross-section o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 95 publications
0
6
0
1
Order By: Relevance
“…Because environmental, ethical, and health values may influence intention and moderate the effect of other predictors [ 43 , 44 , 45 ], we explored potential direct and indirect roles of values on intentions and behaviors. Furthermore, due to the documented role of perceived benefits, perceived susceptibility, perceived severity, subjective norms, and moral satisfaction in explaining dietary and health-related behavior changes [ 34 , 35 , 37 , 45 , 46 , 47 , 48 ], we explored the extent by which these predictors explained changes in intentions and intake.…”
Section: Theoretical Frameworkmentioning
confidence: 99%
“…Because environmental, ethical, and health values may influence intention and moderate the effect of other predictors [ 43 , 44 , 45 ], we explored potential direct and indirect roles of values on intentions and behaviors. Furthermore, due to the documented role of perceived benefits, perceived susceptibility, perceived severity, subjective norms, and moral satisfaction in explaining dietary and health-related behavior changes [ 34 , 35 , 37 , 45 , 46 , 47 , 48 ], we explored the extent by which these predictors explained changes in intentions and intake.…”
Section: Theoretical Frameworkmentioning
confidence: 99%
“…• Individuals can be highly dependent on their social networks (especially family members) for emotional support in coping with a condition, as well as for assistance in making adjustments to dietary and lifestyle habits [ 35 37 ]…”
Section: Resultsmentioning
confidence: 99%
“…For many people, how a health condition is understood and experienced is reliant on their immediate network of support, frequently consisting of their family. This is perhaps a consequence of—and reinforced by—the central importance of family in many populations within collectivist cultures and/or the salience of the condition due to its high prevalence in certain communities [ 35 37 ]. A qualitative study exploring diabetes illness representations in a predominantly Black sample similarly found that participants frequently related their own concerns to family members’ disease-related complications [ 40 ].…”
Section: Resultsmentioning
confidence: 99%
“… 14 The theory assumes that people’s health behaviours may be influenced by five dimensions of health beliefs: perceived susceptibility, perceived severity, perceived benefits, perceived barriers, and cues to action. 15 , 16 HBM is widely used to explain and predict health behavior changes, such as vaccination, 17 disease screening 18 and treatment compliance of diabetic patients, 19 and to guide interventions to improve patients’ self-care behavior, such as blood glucose self-test, 20 and physical exercise. 21 However, it is rarely used to explain the blood glucose management of elderly patients with type 2 diabetes in Chinese community.…”
Section: Introductionmentioning
confidence: 99%